2011
DOI: 10.1016/j.genhosppsych.2011.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic association of depression following myocardial infarction with mortality and cardiovascular events: a meta-analysis of 25 years of research

Abstract: Post-MI depression is associated with a 1.6- to 2.7-fold increased risk of impaired outcomes within 24 months. This association has been relatively stable over the past 25 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
298
3
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 450 publications
(346 citation statements)
references
References 39 publications
12
298
3
11
Order By: Relevance
“…In addition, our findings are also in line with meta-analyses that showed that depressive symptoms following MI are a stronger predictor of mortality than cardiovascular events [Meijer et al, 2011;Meijer et al, 2013a], suggesting that the potential effect of depression on medical illness is not specific for heart disease. On the other hand, it could also be that depressive symptoms are only predictive of specific events, such as (acute) ischemic events, or that only specific depressive symptoms, excluded from our study, are related to non-fatal cardiac events, or that depressive symptoms are predictive of non-fatal cardiovascular events at short-term but not at long-term follow-up.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, our findings are also in line with meta-analyses that showed that depressive symptoms following MI are a stronger predictor of mortality than cardiovascular events [Meijer et al, 2011;Meijer et al, 2013a], suggesting that the potential effect of depression on medical illness is not specific for heart disease. On the other hand, it could also be that depressive symptoms are only predictive of specific events, such as (acute) ischemic events, or that only specific depressive symptoms, excluded from our study, are related to non-fatal cardiac events, or that depressive symptoms are predictive of non-fatal cardiovascular events at short-term but not at long-term follow-up.…”
Section: Discussionsupporting
confidence: 90%
“…The relevance of the presence of anxiety and depression in cardiac patients has repeatedly been shown in systematic reviews; both are associated with higher death rates and poorer prognoses in general in cardiovascular disease (3)(4)(5).…”
mentioning
confidence: 89%
“…Its prevalence ranges from 6.6% to 21% across countries (Kessler and Bromet, 2013), rising to 18.3% in Qatar (Bener et al, 2015). Nearly 20% of patients with heart disease suffer from depression (Carney and Freedland, 2008;Elderon and Whooley, 2013;Thombs et al, 2006), while depression following myocardial infarction is associated with 2.25-to 2.38-fold risk of all-cause mortality and 2.59-to 2.71-fold risk of cardiac mortality (Meijer et al, 2011;van Melle et al, 2004). In patients with heart failure, depression is associated with 51% increased risk of all-cause mortality and 119% increased risk of cardiac mortality (Fan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%